Frequency of anemia and hepcidin level in Behcet's disease. - Isik, Ahmet; Koca, Suleyman S. (Wiley-Liss, 2006)
[Abstract Not Available]
70th Annual Scientific Meeting of the American-College-of-Rheumatology/41st Annual Scientific Meeting of the Association-of-Rheumatology-Health-Professionals -- NOV 10-15, 2006 -- Washington, DC